Prehospital and Emergency Department Capacity for Acute Stroke Care in Minnesota - Albert Wu Tsai, PhD, MPH (Centers for Disease Control and Prevention, 2008)
IntroductionStroke is the third leading cause of death in Minnesota. One strategy to reduce the burden of stroke is to implement systems-level improvements in the prehospital and acute care settings. Two surveys conducted in 2006 obtained information about current practices and capacities of emergency medical services and emergency departments in Minnesota.MethodsIn 2006, the Minnesota Department of Health and the Minnesota Stroke Partnership (the statewide stroke collaborative group) conducted two surveys. The survey for emergency medical services organizations, mailed to every licensed ambulance service in Minnesota, asked about transportation policies and training needs. The survey for hospitals, mailed to every hospital in the state, asked about capacity to treat acute stroke. Results were calculated using simple frequency analyses.ResultsOf 257 surveys mailed to ambulance services, 199 (77%) were returned. Ambulance services generally considered stroke an emergency. Training on stroke was reported most effective in person annually or semiannually. Of 133 surveys mailed to hospitals, 120 (90%) were returned. Stroke capacity differed markedly between hospitals in rural areas and hospitals in the large Minneapolis-St. Paul metropolitan area. Many hospitals, particularly small hospitals, reported lacking stroke protocols. Training for stroke is needed overall but particularly in small hospitals.ConclusionTransport and treatment of people with acute stroke in Minnesota vary by hospital size and location. Standardization of transport and protocols for acute treatment may increase efficiency and overall care for stroke patients. In addition, the need to train ambulance personnel and emergency departments about stroke remains high.